Characteristics of Root Canal Filling Materials for Primary Teeth: A Review of Literature - Zargar, Nazanin; Rezvani, Yasaman; babaie, Sindokht; Eftekhar, Leila (Journal of Dental School, 2022)
Objectives Different root canal filling materials show different clinical and radiographic success rates. Since there is controversy on the best root canal filling material in primary dentition, the aim of this study was to summarize information about root canal filling materials for primary teeth in terms of biocompatibility, cytotoxicity, resorption rate, and survival rate. Methods By searching online databases, studies that addressed biocompatibility, cytotoxicity, resorption, and survival rates of different root filling materials in primary teeth from 1985 to 2020 were evaluated and the required data were extracted. The results were tabulated and compared. Results Due to methodological discrepancies, different studies show different and sometimes inconsistent results, which make it hard to reach a final conclusion; but it seems that Vitapex and Maisto's paste are more biocompatible and have a good survival rate. Zinc oxide eugenol (ZOE) and calcium hydroxide have lower cytotoxicity among different filling materials. However, due to low resorption rate, ZOE can affect permanent successors. Conclusion Based on the unique characteristics of each patient, different filling materials may be used for a clinically optimal dental treatment.